2008
DOI: 10.1002/chin.200807051
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Practical and Robust Method for Regio‐ and Stereoselective Preparation of (E)‐Ketene tert‐Butyl TMS Acetals and β‐Ketoester‐Derived tert‐Butyl (1Z,3E)‐1,3‐Bis(TMS)dienol Ethers.

Abstract: Ketenes and derivatives P 0230 Practical and Robust Method for Regio-and Stereoselective Preparation of (E)-Ketene tert-Butyl TMS Acetals and β-Ketoester-Derived tert-Butyl (1Z,3E)-1,3-Bis(TMS)dienol Ethers. -(OKABAYASHI, T.; IIDA, A.; TAKAI, K.; NAWATE, Y.; MISAKI, T.; TANABE*, Y.; J. Org. Chem. 72 (2007) 21, 8142-8145; Dep. Chem., Sch. Sci. Technol., Kwansei Gakuin Univ., Sanda, Hyogo 669, Japan; Eng.) -Jannicke

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…46 Stereoselective Preparation of (E)-Ketene Trimethylsilyl Acetals (KSAs) in CPME. Okabayashi et al in 2007, investigated the synthesis of ketene silyl acetals (KSAs), 47 a highly demanding ester employed as a reactive precursor in various organic reactions such as Mukaiyama aldol and Michael reactions, Ireland−Claisen rearrangement, Diels− Alder reaction, etc. Following this, tert-butyl ester has been enolized with lithium diisopropylamide (LDA) at 0−5 °C followed by trapping with TMSCl in ether solvent (Scheme 18).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Stereoselective Preparation of (E)-Ketene Trimethylsilyl Acetals (KSAs) in CPME. Okabayashi et al in 2007, investigated the synthesis of ketene silyl acetals (KSAs), 47 a highly demanding ester employed as a reactive precursor in various organic reactions such as Mukaiyama aldol and Michael reactions, Ireland−Claisen rearrangement, Diels− Alder reaction, etc. Following this, tert-butyl ester has been enolized with lithium diisopropylamide (LDA) at 0−5 °C followed by trapping with TMSCl in ether solvent (Scheme 18).…”
Section: ■ Introductionmentioning
confidence: 99%
“…42 The solvent screening effect concludes that the best result was obtained by CPME with regards to both yield (80%) and regioselectivity (>97:3), whereas the use of Et 2 O, THF, dioxane, and DME resulted in poor regioselectivity with the formation of undesirable C-silylation (B). 47 To be noted that the use of a bulky tert-butyl group also promotes stereoselectivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The reactions were conducted under mild conditions, 0−5 °C, 2.5 h and produced both (E)-KSAs and 1,3bis(TMS)-KSAs, see Scheme 71. 359 α-Oxygen and α -nitrogensubstituted t-butyl esters were also shown to be compatible with this methodology. During solvent screening for reaction condition optimization, it was shown that other ethereal solvents such as diethyl ether, THF, 1,4-dioxane, and dimethoxyethane led to poor regioselectivity and C-silylation, whereas CPME by comparison outperformed all of these solvents.…”
Section: Amide Bond Formationmentioning
confidence: 90%